ANALISIS BIAYA KECELAKAAN LALULINTAS DI KOTA MAKASSAR - Muhtar, Munawir; Ali, Nur; Ramli, Muh. Isran (Jurnal Transportasi, 2007)
AbstractÂ This study intended to investigate the traffic accident cost in the city of Makassar.Â  Analysis performed in this study used two components of accident costs, namely resource and non-resource costs. The Resource costs include cost for repairing vehicles, hospital costs, and production loss. The non-resource costs include costs related to pain, grief and mourn, and other costs paid by family and friends. In this study, the Gross of Output Method was used for analysis. Data for traffic accident victim were collected from hospitals and accident cost data were obtained from the victims, using interview techniques and questionnaires. The results of this study show that the costs for every victim accident category in the city of Makassar are for victim die is equal to Rp. 114,516,00,-, Rp. 60,008,599,-, Rp. 1,525,990,-, and Rp. 517,500,- for fatality, serious injury, slight injury, and property damage only, respectively.Keywords: traffic accident, traffic accident victim, fatality